Problem with two-point conditions for parabolic equation of second order on time - Symotyuk, M.M.; Tymkiv, I.R. (Carpathian Mathematical Publications, 2014)
The correctness of the problem with two-point conditions on time variable and Dirichlet-type conditions on spetial coordinates for the linear parabolic equations are established. The metric theorem about estimate from below of small denominators of the problem is proved.